Джерела з історії морських навчальних закладів Півдня України останньої чверті ХVІІІ – початку ХХ ст. - Чорний, О. (Архіви України, 2008)
The article covers the source base (archival documents from the state archives of Ukraine and archives publications of XIX – XX centuries) with regard to history of educational institutions specializing in training naval officers for the Black Sea navy and merchant marine.